Kinesiology taping and lower limb muscle activation: a systematic review and meta-analysis in athletes and healthy adults - Raza, A.; Zaki, S.; Zafar, T.; Alam, M. F.; Sharma, S.; Aysha, T. (Trends in Sport Sciences, 2026)
Introduction: Kinesiology taping (KT) is frequently applied in sports and rehabilitation settings to influence muscle activation and enhance performance. However, its effectiveness remains inconclusive, especially among healthy individuals and athletes. Aim of Study: This systematic review and metaanalysis aimed to synthesize current evidence on the effects of KT - including both facilitatory and inhibitory techniques - on lower limb muscle activation. Materials and Methods: A comprehensive search was conducted across six electronic databases (Cochrane CENTRAL, Web of Science, Scopus, MEDLINE, PubMed, and PEDro) from inception to December 2023. Randomized controlled trials (RCTs) evaluating the effects of KT on surface electromyographic (sEMG) outcomes - including muscle activation amplitude (e.g., root mean square, percentage of maximum voluntary isometric contraction) and activation duration (onset/offset timing) - in lower limb muscles (e.g., gastrocnemius, rectus femoris, vastus medialis, vastus lateralis, gluteus medius) were included. Risk of bias was assessed, and the GRADE approach was used to evaluate the certainty of evidence. Results: Ten RCTs comprising 356 participants (162 athletes, 194 healthy adults) met the inclusion criteria. These included two-arm, three-arm, and crossover designs, reflecting diverse experimental methodologies; three trials were eligible for meta-analysis. The studies employed two-arm, three-arm, and crossover designs, with KT durations ranging from immediate application to 72 hours. Six studies reported increased muscle activation following KT, including unexpected enhancements from inhibitory KT (IKT). Meta-analysis of three RCTs showed a small, statistically nonsignificant effect of IKT on lower limb muscle activation compared to control (standardized mean difference [SMD] = 0.20; 95% CI: -0.20 to 0.59; I2 = 0%, p = 0.33). Limitations: Heterogeneity in taping protocols, participant populations, and limited blinding mayaffect the generalizability and certainty of the findings. Conclusion: While individual studies suggest that KT may enhance muscle activation - particularly when applied in a facilitatory manner over extended durations - the overall evidence remains inconsistent. Meta-analysis revealed a small, statistically nonsignificant effect of IKT, indicating that its clinical efficacy in improving muscle activation, as measured by surface electromyography, remains uncertain and contextdependent. Further high-quality, standardized research is warranted.